The relationship of viral antigen to virus-induced defects in chick embryos. Newcastle disease virus - Williamson, Alice P.; Blattner, Russell J.; Robertson, G.Gordon (Developmental biology, 1965)
Results indicate that the developmental defects observed in chick embryos following inoculation of Newcastle disease virus at 36, 48, and 60 hours' incubation are due to sloughing and necrosis of cells in specifically differentiating organs following replication of viral antigen in cells of such tissues. Although replication of viral antigen is not limited to these structures, minimal cell damage is observed in other structures within the time limits of the study. Using immunofluorescent staining techniques, the viral antigen is consistently observed first, at 6–8 hours postinoculation, in cells of the extraembryonic structures, i.e., ectoderm of somatopleure and amnion and endoderm of splanchnopleure. In tissues of the embryo, specific fluorescence begins to appear at 10–12 hours postinoculation; it is first concentrated in structures differentiating from the body ectoderm. The pattern of fluorescence conforms in general to structures previously observed to be susceptible to teratogenic effects or microscopic pathological changes. Structures consistently affected include lens, auditory epithelium, visceral arch ectoderm, olfactory epithelium, and caudal neural tube. The optic cups and the brain, which is closed off and separated from the body ectoderm at the time of inoculation, show no evidence of infection. As infection progresses the specific fluorescence is observed in more of the general body ectoderm and invasion is also observed in the underlying mesoderm, where it is located chiefly in visceral arches, somites, epimyocardium of the heart, and endothelium of capillaries that lie in affected areas of the mesoderm.